Relevance of funding information - De-Castro, Pablo (Anuario ThinkEPI, 2018)
Open access implementation seems to have reached a plateau in many countries, and as a result the push for open science frequently places more emphasis on research data management. There are, however, whole areas around the open communication of research outputs which can still benefit from significant improvement. One of the most obvious is a better codification of the funding information in the bibliographic records for publications in repositories. While the emphasis has traditionally been to collect as many full-text records as possible about institutional and subject-based repositories, the typical way the funding information for publications is being coded into metadata records remains very poor, or is absent altogether. This paper argues that this is a key area for research impact assessment and improvement. It´s also argued that such an improvement needs solid housekeeping on the research funders´ side, possibly based on new and evolving standards. A few different approaches to capture and display the funding information in metadata records in an optimal fashion are discussed.
Keywords: Research information management; Funding information; Research outputs; Metadata; Research funders; Research impact; Open access.